Mandala Coloring as Jungian Art to Reduce Bullying and Increase Social Skills - Anahita Khodabakhshi-Koolaee; Faezeh Darestani-Farahani (Iran University of Medical Sciences, 2020)
Background: Bullying and the lack of social skills are essential for future risk-related problems, such as delinquency and feelings of rejection in children. The present study aimed to assess the effects of coloring mandala as Jungian art to reduce bullying and increase social skills in Afghan male working children. Methods: It was a quasi-experimental study with a pre-test, post-test and a control group design. The research population included all 10- to 12-year-old Afghan immigrant boys in Tehran City, Iran, who were studying in Parto School for Working Children, in 2019. The research sample consisted of 30 children who have obtained maximum scores on the Illinois Bully Scale (IBS) and minimum scores on the Teenage Social Skills Inventory (TSSI). The research participants were selected using a convenience sampling method. Then, they were assigned to the control and treatment groups by drawing lots. The treatment group attended ten 45-minute sessions of coloring mandalas and Jungian art. The data collection tools were the IBS: Student Version (Espelage & Holt, 2001) and the TSSI (Inderbitzen & Foster, 1992). The data were analyzed using the one-way Analysis of Covariance (ANCOVA) in SPSS. Results: The present research results suggested that the bullying scores for the participants in the treatment group significantly decreased at the post-test, compared to the pre-test (F=24.29, P=0.001); however, their social skills scores significantly increased at the post-test, in comparison with the pre-test (F=42.41, P=0.001). However, no significant differences were found in the bullying and social skills scores of the controls between the pre-test and post-test phases.  Conclusion: Mandala coloring art was effective in reducing bullying behaviors and increasing social skills among the explored Afghan migrant working children. Therefore, this artistic method can be used as a suitable option for psychological therapies, teaching social skills, and creating participation and empathy in children in educational centers and schools for child labor.